Informed consent for paradata use in web surveys. (July 2020) - Kunz, Tanja; Landesvatter, Camille; Gummer, Tobias
Paradata are a valuable source of information to better understand the response process and to determine how the data collection processes can be improved. Currently, a debate is ongoing in academia and in the professional associations of market, opinion, and social research concerning the need to inform respondents about the collection and use of their web paradata. Unfortunately, research is lacking on the design of informed consent for web paradata use and its possible consequences for respondents' willingness to share their paradata, completion of a survey, and response behavior. The aim of this study is to provide guidance to the survey practitioner on the optimal design of informed consent for web paradata use based on experimental evidence.